Shoulder Tuberculosis: Management of a Posteriori Diagnosis After a Reverse Prosthesis Implantation - Giordano G.; Lourtet-Hascoët J.; Martin Blondel G.; Bonnet E. (Case Reports in Infectious Diseases)
We report a rare case of reverse shoulder prosthesis implantation in a patient retrospectively showing a chronic tuberculous osteoarthritis and meningitis. In this atypical presentation, the patient presented only a chronic shoulder pain, with no clinical or imaging sign of tuberculosis. After the implantation of a reverse shoulder prosthesis, the patient presented a reactivation of a tuberculosis causing a meningitis. The diagnosis of shoulder osteoarthritis caused by M. tuberculosis was confirmed retrospectively on deep perioperative samples by standard culture, PCR, and positive pathology. The management of the patient consisted in 12 months of a medical antituberculosis therapy and showed a favorable outcome.